PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KVISOFT UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI MEDAN MAGNET - I Dewa Putu Leo Parlin; Bambang Heru Iswanto; Agus Setyo Budi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
This research aims to improve understanding of the concept of learning physics through media-based learning materials kvisoft the magnetic field. The method used in this research is research and development. This research was conducted in INDOCEMENT high school in the academic year 2014/2015. Before the planning by creating a story board, prototype, flowchard, and development schedule. The software used to develop learning media are kvisoft software. Media Learning physics is limited to the material's magnetic field on the class XII. For the validation conducted by two experts and two experts media material, followed by a test of small groups, large groups and outreach to the larger community, along with a revision after tested. Development of the model used is based on Borg and Gall with comparative descriptive data retrieval. Kvisoft based learning media development is expected to improve understanding of the concept of students in the material's magnetic field. Keywords: Kvisoft, pemahaman konsep, medan magnet.